ARAH POLITIK HUKUM PENGATURAN DESA KE DEPAN (IUS CONSTITUENDUM) - Retno Saraswati (Faculty of Law, Universitas Diponegoro, 2014)
Legal policy of the village regulation (Law number 6 year 2014) is remain inconsistent with legal policy constitution.The Methods of research is normative juridical approach and analyse the secondary data and information gathered. The results indicated that the legal policy of village regulation stipulate that educational requirements for village heads should be minimum of high school or its equivalent; village heads tenure should be two period only; and the rural development planning of village does not necessary brought to the same direction or template of the planning from higher government level such as regency. Abstrak Politik hukum pengaturan mengenai desa yang tertuang dalam Undang Undang Nomor 6 Tahun 2014 tentang Desa ternyata masih mengandung inkonsistensi terhadap politik hukum dalam konstitusi. Penelitian ini menggunakan metode pendekatan yuridis normatif, dengan data sekunder sebagai sumbernya. Hasil penelitian menunjukkan bahwa pengaturan desa ke depan seharusnya memperhatikan persyaratan pendidikan kepala desa minimal sekolah lanjutan atas, rentang masa jabatan kepala desa, dan perencanaan pembangunan desa tidak memaksakan untuk mengacu pada perencanaan pembangunan daerah di atasnya.